US Astronomical Photographic Data Archives: Hidden Treasures and Importance for High-Energy Astrophysics - René Hudec; Lukáš Hudec (Acta Polytechnica CTU Proceedings, 2014)
We report here on an ongoing investigation of US astronomical plate archives and tests of the suitability of transportable scanning devices for in situ digitization of archival astronomical plates, with emphasis on application in high-energy astrophysics.